The apparent genetic anticipation in PMS2-associated lynch syndrome families is explained by birth-cohort effect - Ten Broeke, Sanne W.; Knebel Doeberitz, Magnus von (Cancer epidemiology, biomarkers & prevention, 2019)
Background: PMS2-associated Lynch syndrome is characterized by a relatively low colorectal cancer penetrance compared with other Lynch syndromes. However, age at colorectal cancer diagnosis varies widely, and a strong genetic anticipation effect has been suggested for PMS2 families. In this study, we examined proposed genetic anticipation in a sample of 152 European PMS2 families. - Methods: The 152 families (637 family members) that were eligible for analysis were mainly clinically ascertained via clinical genetics centers. We used weighted Cox-type random effects model, adjusted by birth cohort and sex, to estimate the generational effect on the age of onset of colorectal cancer. Probands and young birth cohorts were excluded from the analyses. Weights represented mutation probabilities based on kinship coefficients, thus avoiding testing bias. - Results: Family data across three generations, including 123 colorectal cancers, were analyzed. When compared with the first generation, the crude HR for anticipation was 2.242 [95% confidence interval (CI), 1.162-4.328] for the second generation and 2.644 (95% CI, 1.082-6.464) for the third generation. However, after correction for birth cohort and sex, the effect vanished [HR = 1.302 (95% CI, 0.648-2.619) and HR = 1.074 (95% CI, 0.406-2.842) for second and third generations, respectively]. - Conclusions: Our study did not confirm previous reports of genetic anticipation in PMS2-associated Lynch syndrome. Birth-cohort effect seems the most likely explanation for observed younger colorectal cancer diagnosis in subsequent generations, particularly because there is currently no commonly accepted biological mechanism that could explain genetic anticipation in Lynch syndrome. - Impact: This new model for studying genetic anticipation provides a standard for rigorous analysis of families with dominantly inherited cancer predisposition.
Gesehen am 24.02.2020